Ecobrick Sebagai Representasi Pemberdayaan Hutan Adat Desa Beruas - Fadillah, Laila; Al Farisi, Arief Abiyyu; Rahmadani, Astrid; Saputra, Abil (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
The beginning of the establishment of Customary Forests in Beruas Village, Kelapa District, West Bangka Regency was in the 1980s. At that time, several people from Beruas Village entered the wilderness with the initial intention of planting rice, but were allowed to take wood to make houses in the Beruas area, both in the village and in the garden, so as not to look outside. because it is in the customary forest agreed with their grandfather. The late grandfather Isa and Muhidin turned out to be cousins. Over time, the Customary Forest has a land area of 100 hectares which has an impact on the physical development activities of roads and Village assets. It is estimated that the West Bangka Forestry Service certificate was made yesterday, the area is still 85 hectares intact. The customary forest certificate was issued in 2016 during the administration of the Regent of West Bangka, Ustadz Zuhri. and Deputy Regent Mr. Haji Sukirman. Apart from that, wood in Customary Forests cannot be traded, especially for the Beruas Village community, for free.